Ability‐grouping and problem behavior trajectories in childhood and adolescence: Results from a U.K. population‐based sample. Issue 2 (29th September 2021) - Papachristou, Efstathios; Flouri, Eirini; Joshi, Heather; Midouhas, Emily; Lewis, Glyn
Abstract: Ability‐grouping has been studied extensively in relation to children's academic, but not emotional and behavioral outcomes. The sample comprised 7259 U.K. children (50% male) with data on between‐class and within‐class ability‐grouping at age 7. Peer, emotional, hyperactivity, and conduct problems were measured at ages 7, 11, and 14 years. Children in low within‐class ability groups showed more hyperactivity and emotional problems across the study period compared to non‐grouped children, after adjustments for the different types of ability grouping and confounding. Additionally, children in the middle within‐class ability groups showed more, and those in the top within‐class groups less, hyperactivity compared to non‐grouped children, after adjustment. Children in lower within‐class groups should be monitored closely to ensure that their well‐being is not compromised.